A mixed-methods approach to leadership styles in small and medium sized businesses in Uganda - Nyakato, Elizabeth; Alasan , Imran Ibrahim (Eximia, 2022)
Although there have been many studies on leadership, very little has been done on small and medium-sized businesses (SMEs). The goal of this study is to recognise and comprehend leadership styles in SMEs while taking into account the importance of this research issue. Three Ugandan SMEs used a mixed-method strategy to accomplish this (multiple case studies). Data came from the Multifactor Leadership Questionnaire (MLQ), SME collaborators, and owner-manager/leader interviews. The analyses utilised were descriptive and content-based. The results confirmed that leadership plays a crucial part in SME management. In the SMEs chosen, various levels of leadership outcomes were found. The results thus provide more evidence for the claim that leadership is crucial for successful management in SMEs. The discussion also includes how the findings might be put to use in the future.